2019
DOI: 10.1073/pnas.1907490116
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1–C1q complexes regulate macrophage function by switching between leukotriene and specialized proresolving mediator biosynthesis

Abstract: Macrophage polarization is critical to inflammation and resolution of inflammation. We previously showed that high-mobility group box 1 (HMGB1) can engage receptor for advanced glycation end product (RAGE) to direct monocytes to a proinflammatory phenotype characterized by production of type 1 IFN and proinflammatory cytokines. In contrast, HMGB1 plus C1q form a tetramolecular complex cross-linking RAGE and LAIR-1 and directing monocytes to an antiinflammatory phenotype. Lipid mediators, as well as cytokines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 72 publications
2
58
0
Order By: Relevance
“…Furthermore, we recently reported that RvD2 induces active resolution of inflammation through pulp-like tissue regeneration after root canal infection (80). It is possible that the HMGB1-C1q complex induces the production of RvD2 for dental pulp regeneration, as suggested by Liu et al (25).…”
Section: Dental Pulp Regenerationmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, we recently reported that RvD2 induces active resolution of inflammation through pulp-like tissue regeneration after root canal infection (80). It is possible that the HMGB1-C1q complex induces the production of RvD2 for dental pulp regeneration, as suggested by Liu et al (25).…”
Section: Dental Pulp Regenerationmentioning
confidence: 71%
“…On the other hand, the C1 complex (C1q), which normally triggers the classical pathway, is thought to regulate both inflammation and regeneration by the coexistence of DAMPs. Liu et al (25) reported that the HMGB1-C1q complex induces production of proresolving mediators such as resolvin (Rv)D1 and RvD2. The resolution of inflammation and macrophage polarization may result in tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that HMGB1 through a positive feedback loop involving IRF5 increases leukotriene B4 production in activated monocytes while HMGB1 plus C1q increase the production of specialized pro-resolving lipid mediators (82). In the same study, a fusion protein that contains the RAGEbinding fragment of HMGB1 and the LAIR-1-binding fragment of C1q were shown to crosslink the two receptors the same way HMGB1 and C1q do and to exert the same pro-resolving effects both in vivo and in vitro (82). Recognizing that HMGB1 can be harnessed to enhance tolerogenic properties of the immune system opens up novel opportunities for potential therapeutics.…”
Section: Hmgb1-based Therapeuticsmentioning
confidence: 99%
“…98 Moreover, a complement factor C1q also interacted with HMGB1 (K D = 200 nM) and formed a tetramolecular complex with RAGE and LAIR-1, resulting in the production of anti-inflammatory cytokines (eg, IL-10) and proresolution lipid mediators. 99,100 Thus, in a sharp contrast to exogenous PAMPs (eg, CpG-DNA and LPS), many endogenous proteins can bind HMGB1 to tilt the balance towards anti-inflammatory responses via distinct signaling pathways. 95,[98][99][100]…”
Section: Endogenous Hmgb1-binding Proteinsmentioning
confidence: 99%
“…99,100 Thus, in a sharp contrast to exogenous PAMPs (eg, CpG-DNA and LPS), many endogenous proteins can bind HMGB1 to tilt the balance towards anti-inflammatory responses via distinct signaling pathways. 95,[98][99][100]…”
Section: Endogenous Hmgb1-binding Proteinsmentioning
confidence: 99%